2018
DOI: 10.1200/jco.2017.77.4893
|View full text |Cite
|
Sign up to set email alerts
|

American Society of Clinical Oncology Statement: Biosimilars in Oncology

Abstract: As many biosimilars come to market in the next several years, their use in oncology will play an important role in the future care of patients with cancer. ASCO is committed to providing education and guidance to the oncology community on the use of biosimilars in the cancer setting; therefore, ASCO has developed this statement to offer guidance in the following areas: (1) naming, labeling, and other regulatory considerations, (2) safety and efficacy of biosimilars, (3) interchangeability, switching, and subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
105
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(105 citation statements)
references
References 2 publications
0
105
0
Order By: Relevance
“…Despite the increasing use of internet health information by patients, one survey found that perceived physician quality had a greater impact on treatment compliance than the perceived quality of internet health information [178], emphasizing the importance of HCP communication. In addition, educational materials developed by medical societies or government organizations, in conjunction with patient groups, could play a key role in supporting patient education about biosimilars, as recognized in the oncology setting [179].…”
Section: Patients' Perspective: Improved Information Sharing May Encomentioning
confidence: 99%
“…Despite the increasing use of internet health information by patients, one survey found that perceived physician quality had a greater impact on treatment compliance than the perceived quality of internet health information [178], emphasizing the importance of HCP communication. In addition, educational materials developed by medical societies or government organizations, in conjunction with patient groups, could play a key role in supporting patient education about biosimilars, as recognized in the oncology setting [179].…”
Section: Patients' Perspective: Improved Information Sharing May Encomentioning
confidence: 99%
“…However, interchangeability is not automatically granted upon approval of a biosimilar; additional evidence is required to demonstrate that the clinical result achieved with the biosimilar is expected to be the same as the reference product. In addition, switching treatment between the reference product and biosimilar should demonstrate no increased risk to the patient …”
Section: Regulatory Approval Of Biosimilars: Global Versus Latin Amermentioning
confidence: 99%
“…the assessment of a licensed biologic that has undergone a manufacturing process change) [16,47,48]. Educational materials released by the European Medicines Agency (EMA) and the United States Food and Drug Administration (FDA), as well as initiatives from medical societies emphasize the need to increase understanding of biosimilars among patients and healthcare professionals [49][50][51].…”
Section: Expert Opinionmentioning
confidence: 99%